PENINGKATAN KEAKTIFAN DAN PRESTASI BELAJAR FISIKA MATERI GERAK LURUS MELALUI PEMBELAJARAN DARING BERBASIS WHATSAPP GROUP SISWA KELAS X IPA-1 SMA NEGERI 1 SIBORONGBORONG SEMESTER 2 TAHUN PELAJARAN 2020/2021 - Jan Piter Saragih (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2021)
The purpose of this research is to increase the activeness and learning achievement of students in learning physics in straight motion material with online learning based on Whatsapp Group. The type of research is classroom action research. The research subjects were 18 students. Data collection techniques using test techniques, observation and documentation. Data validation is done by triangulation. Data analysis used descriptive analysis of percentage technique. The results showed that the activeness of students in the initial study was only 12 students or 33.33%, increased to 23 students or 63.89% in the first cycle, and 94.44% or 34 students in the second cycle. The increase in student learning outcomes from the average in the initial study of 65.83 rose to 73.82 in the first cycle, and 85.28 in the second cycle, with a learning completeness level of 9 students (25%) in the initial study, increasing to 50% or 18 students in the first cycle, and 33 students or 91.67% in the second cycle.